Letter to Jane Tolmach from Thomas E. Laubacher - Thomas E. Laubacher:::::: (1966)
A letter from Thomas E. Laubacher that congratulates Jane Tolmach on her election as Women's Chairman for Southern California of the Democratic State Central Committee.